2008
DOI: 10.1785/0120070218
|View full text |Cite
|
Sign up to set email alerts
|

Regional Attenuation in Northern California: A Comparison of Five 1D Q Methods

Abstract: The determination of regional attenuation Q -1 can depend upon the analysis method employed. The discrepancies between methods are due to differing parameterizations (e.g., geometrical spreading rates), employed datasets (e.g., choice of path lengths and sources), and the methodologies themselves (e.g., measurement in the frequency or time domain). Here we apply five different attenuation methodologies to a Northern California dataset. The methods are: (1) coda normalization (CN), (2) two-station (TS), (3) rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Therefore, spreading transitions from a spherical to a cylindrical type at approximately 100 km. FORD et al (2008) found that results differed only slightly when r 0 is between 60 and 120 km. For brevity we will refer to this method as AMP (for AMPlitude).…”
Section: Data Set and Attenuation Tomography Techniquesmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, spreading transitions from a spherical to a cylindrical type at approximately 100 km. FORD et al (2008) found that results differed only slightly when r 0 is between 60 and 120 km. For brevity we will refer to this method as AMP (for AMPlitude).…”
Section: Data Set and Attenuation Tomography Techniquesmentioning
confidence: 90%
“…Q models taken from the literature can vary greatly within the same region. In previous work (FORD et al, 2008), we compared five different 1-D methods to measure Q Lg and attempted to assess the error associated with the results. The assessment showed the possible influence of lateral variations in attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…The site V S30 values are taken from the Next Generation Attenuation-West 2 (NGA-West 2) site database if they are available; otherwise, we take the closest value from the gridded V S30 map of Wills et al (2000; and Kalkan (2015) GMPE, however, uses Q 0 as a frequencyindependent input independent variable that can be changed for each realization of the GMPE; for the case of the South Napa earthquake, Q 0 50. This is motivated partially to fit the data and also to be within the range suggested by Ford et al (2008) for the San Francisco Bay area (Erol Kalkan and Vladimir Graizer, personal comm., 2014). The Chiou and Youngs (2014) GMPE has the option of implementing the effect of directivity, specific for the fault geometry and the station distance and location, using the direct-point parameter (DPP) described in chapter 5 of Spudich et al (2013).…”
Section: Ground-motion Datamentioning
confidence: 98%
“…Examples are Ford et al (2008) and Negi et al (2015). Although using coda waves, the method is independent of the scattering model used for coda waves and the results are therefore not directly comparable with coda Q.…”
Section: Introductionmentioning
confidence: 99%
“…For Lg coda Q studies, Mitchell et al (2015) pointed out the importance of using the same procedures and parameters and claim to have done so in their many studies. For California, Ford et al (2008) used five different methods, none of which was the CWD method, to determine Lg coda Q and found significant differences due to the varying methods, but also to the choice of parameters. Hellweg et al (1995), in a study of California coda Q, also points out the importance of using the same parameters, in particular lapse time and length of analysis window, when comparing coda Q.…”
Section: Introductionmentioning
confidence: 99%